Land-use intensity mediates ecosystem service tradeoffs across regional social-ecological systems. Issue 1 (1st January 2021) - Qiu, Jiangxiao; Queiroz, Cibele; Bennett, Elena M.; Cord, Anna F.; Crouzat, Emilie; Lavorel, Sandra; Maes, Joachim; Meacham, Megan; Norström, Albert V.; Peterson, Garry D.; Seppelt, Ralf; Turner, Monica G.
ABSTRACT: A key sustainability challenge in human-dominated landscapes is how to reconcile competing demands such as food production, water quality, climate regulation, and ecological amenities. Prior research has documented how efforts to prioritize desirable ecosystem services such as food and fiber have often led to tradeoffs with other services. However, the growing literature has revealed different and sometimes contradictory patterns in ecosystem service relationships. It thus remains unclear whether there are generalizable patterns across social-ecological systems, and if not, what factors explain the variations. In this study, we synthesize datasets of five ecosystem services from four social-ecological systems. We ask: (1) Are ecosystem service relationships consistent across distinct regional social-ecological systems? (2) How do ecosystem service relationships vary with land-use intensity at the landscape scale? (3) In case of ecosystem service tradeoffs, how does land-use intensity affect intersection points of tradeoffs along the landscape composition gradient? Our results reveal that land-use intensity increases magnitude of ecosystem service tradeoffs (e.g. food production vs. climate regulation and water quality) across landscapes. Land-use intensity also alters where provisioning and regulating services intersect: in high-intensity systems, food production and regulating services can be both sustained only at smaller proportions of agricultural lands, whereas in low-intensity systems, these services could be both supplied with greater proportions of agricultural lands. Our research demonstrates importance of considering multiple aspects of land uses (landscape composition and land-use intensity), and provides a more nuanced understanding and framework to enhance our ability to predict how land use alters ecosystem service relationships.